- #1

- 178

- 4

say that dX/dY = 3

now would it be correct if i say that the rate of change of Y with respect to X = 1/3 = dY/dX ?

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter B4ssHunter
- Start date

- #1

- 178

- 4

say that dX/dY = 3

now would it be correct if i say that the rate of change of Y with respect to X = 1/3 = dY/dX ?

- #2

arildno

Science Advisor

Homework Helper

Gold Member

Dearly Missed

- 9,970

- 134

Yes, it is. (but there are many pitfalls in more general situations!)

In YOUR case, suppose you are at point (x_0,y_0), where y_0=Y(x_0), and where dY/dX=3.

That means that in a neigbourhood of (x_0,y_0), Y(x) can be approximated by:

[tex]Y\approx{y}_{0}+\frac{dY}{dx}|_{x=x_{0}}(x-x_{0})[/tex]

That is, you function looks like the straight line:

[tex]y=y_{0}+3(x-x_{0})[/tex]

Locally, you can invert this relation, solving x in terms of "y", and we may write:

[tex]x=x_{0}+\frac{1}{3}(y-y_{0})[/tex]

But, this is "of course", the same as saying, roughly, that dX/dY=1/(dY/dX)=1/3

In YOUR case, suppose you are at point (x_0,y_0), where y_0=Y(x_0), and where dY/dX=3.

That means that in a neigbourhood of (x_0,y_0), Y(x) can be approximated by:

[tex]Y\approx{y}_{0}+\frac{dY}{dx}|_{x=x_{0}}(x-x_{0})[/tex]

That is, you function looks like the straight line:

[tex]y=y_{0}+3(x-x_{0})[/tex]

Locally, you can invert this relation, solving x in terms of "y", and we may write:

[tex]x=x_{0}+\frac{1}{3}(y-y_{0})[/tex]

But, this is "of course", the same as saying, roughly, that dX/dY=1/(dY/dX)=1/3

Last edited:

- #3

- 178

- 4

Yes, it is. (but there are many pitfalls in more general situations!)

In YOUR case, suppose you are at point (x_0,y_0), where y_0=Y(x_0), and where dY/dX=3.

That means that in a neigbourhood of (x_0,y_0), Y(x) can be approximated by:

[tex]Y\approx{y}_{0}+\frac{dY}{dx}|_{x=x_{0}}(x-x_{0})[/tex]

That is, you function looks like the straight line:

[tex]y=y_{0}+3(x-x_{0})[/tex]

Locally, you can invert this relation, solving x in terms of "y", and we may write:

[tex]x=x_{0}+\frac{1}{3}(y-y_{0})[/tex]

But, this is "of course", the same as saying, roughly, that dX/dY=1/(dY/dX)=1/3

okay i understand but i have two questions

what does the underscore you used at the beginning mean ?

in (x_0 ) for instance

and second , in a linear equation , we describe the slope as the coefficient of (y-y0) Or (x-x0) ?

or is it such that the rate of change of y with respect to X is the co-efficient of ( x - xnaught ) and the rate of change of X with respect to y in another equation is the co-efficient of (y-y0) ?

also does this only apply to linear equations ?

- #4

arildno

Science Advisor

Homework Helper

Gold Member

Dearly Missed

- 9,970

- 134

I use (x_0, y_0) to denote a specific point VALUE, to distinguish from the VARIABLES (x,y)

Share:

- Replies
- 1

- Views
- 4K